Potentially Inappropriate Medications in the Elderly in Korean Long-Term Care Facilities - Hwang, Hee-Jin (Drugs Real World Outcomes, 2015)
BACKGROUND: Elderly residents of long-term care facilities are more vulnerable to being prescribed inappropriate medications because of the high incidence of co-medication in this population resulting from the presence of multiple chronic diseases and also age-related changes in pharmacokinetics and pharmacodynamics. OBJECTIVE: We evaluated the frequency of potentially inappropriate medications and factors influencing their frequency. METHODS: A retrospective cross-sectional study was conducted in 20 long-term care facilities located in the northwest regions of South Korea for 824 patients aged 65 years and older who were assessed between January and February of 2012. Potentially inappropriate medications were identified using the 2012 American Geriatric Society’s Beers Criteria. We assessed the relationship between the frequency of potentially inappropriate medications prescribed and patient age, sex, co-medications, comorbidity, activities of daily living, length of stay, grade of long-term care insurance for seniors, and the bed size and business type of the long-term care facility. RESULTS: Of the 529 participants who satisfied our inclusion criteria, 308 (58.2 %) had received at least one inappropriate medication according to the 2012 Beers Criteria. The most frequently prescribed classes of inappropriate medications were central nervous system drugs (58.7 %), anti-cholinergics (21.2 %), and cardiovascular medications (10.8 %). The most commonly used drugs were quetiapine (28.4 %), chlorpheniramine (15.8 %), risperidone (6.5 %), and zolpidem (5.8 %). Inappropriate medication use was associated with the number of co-medications and long-term care insurance grade 3, which means less dependence and a requirement of low-level care. CONCLUSIONS: Central nervous system drugs (58.7 %) were the most prescribed class of inappropriate medications. Quetiapine was the drug most often given inappropriately (28.4 %). There was a relationship between inappropriate medication use and the number of co-medications. The frequency of inappropriate medication prescriptions was higher among patients whose long-term care insurance for seniors was grade 3, which means less dependence and a requirement of low-level care.